2012
DOI: 10.5539/jfr.v1n2p171
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial on the Effects of Tualang Honey and Hormonal Replacement Therapy (HRT) on Cardiovascular Risk Factors, Hormonal Profiles and Bone Density Among Postmenopausal Women: A Pilot Study

Abstract: Results of recent trial have shown some negative effects of HRT on postmenopausal women. Therefore, there has been a need to search for an alternative treatment and honey is one of the well known traditional remedies used in minimizing postmenopausal problems. The objectives of the study were to investigate the effects of Tualang honey on the cardiovascular risk factors, changes in hormonal profiles and also effect on the bone. A randomized controlled trial comparing the effects of Tualang honey 20 g/day and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The mean duration of menopause was 12.13, with a range between 3 and 44 years. In a previous study, the mean duration of menopause was 5.8 years (20). The present study revealed that postmenopausal women are at increased risk of long-term effects such as osteoporosis.…”
Section: Discussionsupporting
confidence: 59%
“…The mean duration of menopause was 12.13, with a range between 3 and 44 years. In a previous study, the mean duration of menopause was 5.8 years (20). The present study revealed that postmenopausal women are at increased risk of long-term effects such as osteoporosis.…”
Section: Discussionsupporting
confidence: 59%
“…The present finding of lower level of serum LH in the J 80 compared to J 20 , HJ 20 and HJ 80 implied that high intensity jumping exercise without honey supplementation may have elicited negative effects on serum LH. This result implies that honey, a high concentrated source of energy with 313 calories per 100 g and antioxidants such as flavonoids and phenolic acid [ 24 ] may have potential to elicit beneficial effects on reduction of adverse effect induced by high intensity jumping exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Chepulis and Starkey [ 23 ] reported that honey feeding alone has shown its beneficial effects on bone mineral density in animals. Additionally, two previous studies have shown that honey has similar effects with hormone replacement therapy on bone densitometry [ 24 ] and prevents uterine atrophy in postmenopausal state [ 25 ]. Nevertheless, these previous studies did not report the underlying mechanisms that could explain the increase in bone mass by honey feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Ariefdjohan et al [10] reported that honey has the potential to increase calcium absorption after 2 days of acute feeding in rats. In addition, Hussain et al [11] reported that honey has similar effects with hormone replacement therapy on bone densitometry in postmenopausal women. Therefore, it was hypothesized that honey may play a role in increasing bone health.…”
mentioning
confidence: 99%